Waves in a generally anisotropic viscoelastic composite laminated bilayer: Impact of the imperfect interface from perfect to complete delamination. (1st October 2020) - Zhu, Feng; Pan, Ernian; Qian, Zhenghua; Luo, Zhe
Abstract: Composite laminates are usually made of anisotropic viscoelastic materials with layer-dependent properties. Although such structures are advantageous over the traditional single-material structure, their interfacial damage/failure is a great concern. In this paper, we present the general formulation and the corresponding solution to enhance our understanding on the guided waves in such laminates with imperfect interfaces. The formulation is based on the modified dual variable and position (DVP) method combined with a powerful and accurate root-finding algorithm. While the former overcomes the numerical instability when handling layered structures, the latter finds all the roots of the dispersion equation in a complex domain providing the full three-dimensional (3D) dispersion curves. After the proposed formulation is validated by the semi-analytical finite-element (SAFE) method for the perfect interface case, the present solution is applied to analyze the dispersion curves and mode shapes for a bilayer laminate with imperfect interface. Numerical examples demonstrate the detailed evolution mechanisms on wave features from perfect interface to complete delamination in the bilayer with imperfect interface. The results presented in this paper provide important insight to guide the in-situ monitoring of the evolution processes of the wave mode shapes and dispersion curves from perfect interface to complete delamination.